2013
DOI: 10.1002/jbm.b.32991
|View full text |Cite
|
Sign up to set email alerts
|

In vitro macrophage response to nanometer‐size chromium oxide particles

Abstract: An increasing number of studies have reported adverse tissue reactions around metal-on-metal (MM) hip implants. However, the origin and mechanisms of these reactions remain unclear. Moreover, the biological effects of nanometer-size chromium oxide particles, the predominant type of wear particles produced by MM implants, remain mostly unknown. The purpose of this study was to analyze the cytotoxic effects of clinically relevant nanometer-size chromium oxide particles on macrophage response in vitro. J774.A1 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…For each experimental condition, 0.5 × 10 6 macrophages were resuspended in 1 ml of DMEM‐based medium containing Co 2+ (2, 4, 8, 16, 24, 32, and 48 ppm) or Cr 3+ (25, 50, 100, 150, 250, 350, and 500 ppm). Macrophages incubated with neither Co 2+ nor Cr 3+ served as a negative control, and macrophages incubated with 1 μg/ml of lipopolysaccharide (LPS) from Escherichia coli O55:B5 (Sigma–Aldrich) were used as a positive control for TNF‐α and CC chemokine release (data not shown), as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each experimental condition, 0.5 × 10 6 macrophages were resuspended in 1 ml of DMEM‐based medium containing Co 2+ (2, 4, 8, 16, 24, 32, and 48 ppm) or Cr 3+ (25, 50, 100, 150, 250, 350, and 500 ppm). Macrophages incubated with neither Co 2+ nor Cr 3+ served as a negative control, and macrophages incubated with 1 μg/ml of lipopolysaccharide (LPS) from Escherichia coli O55:B5 (Sigma–Aldrich) were used as a positive control for TNF‐α and CC chemokine release (data not shown), as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Macrophages incubated with neither Co 2þ nor Cr 3þ served as a negative control, and macrophages incubated with 1 mg/ml of lipopolysaccharide (LPS) from Escherichia coli O55:B5 (Sigma-Aldrich) were used as a positive control for TNF-a and CC chemokine release (data not shown), as previously described. 28 Triplicate samples in loosely capped 5-ml untreated polystyrene culture tubes (BD Biosciences) were incubated under cell culture conditions for 24 h. At the end of the incubation, the macrophage suspensions were centrifuged (150g for 6 min at room temperature), and the supernatants were frozen and stored in siliconized microcentrifuge tubes (Fisher Scientific) at À80˚C for cytokine measurements by enzyme-linked immunosorbent assays (ELISA; R&D Systems, Minneapolis, MN).…”
Section: Tnf-a and Chemokine Releasementioning
confidence: 99%
“…It is known that particles size is inversely proportional to the cytotoxicity degree [28,29], a data that could explain why particles from wear corrosion tests in PBS and in PBS supplemented with 0.3% HA in the absence of anodic polarization elicited a lower macrophages cell biocompatibility, as in these samples a higher proportion of small particles were detected (data not shown). The particles produced in these solutions and in these experimental conditions proceed from the breakdown of the passive film formed in the material surface where an enriched in chromium oxide was observed, a compound with high toxicity [30]. It is also necessary to consider that macrophages assays here reported were done taking in consideration the concentration of particles, that means that for the same total mass the proportion of particles with small size probably is higher in the assays performed in absence of polarization, either in PBS or PBS+0.3% HA, that could also give explanation for the lower macrophage biocompatibility of these particles.…”
Section: Macrophage Cell Responsementioning
confidence: 99%
“…They found that CoCr-alloy particles were by far the most toxic and decreased viability and proliferation of human osteoblasts, fibroblasts, and macrophages. VanOs et al [90] used commercially available 60 nm and 700 nm round chromium oxide (Cr 2 O 3 ) particles to analyse the cytotoxic effects of chromium oxide particles on macrophage responses in vitro. With both particle sizes, cell mortality increased, resulting in a significant decrease in total cell numbers, as well as a significant increase in late apoptosis and necrosis.…”
Section: Toxicitymentioning
confidence: 99%